Intestinal stem cell-mediated repair in Drosophila 2 - Ip, Tony (Henry Stewart Talks, 2014)
The adult Drosophila midgut contains tissue specific intestinal stem cells (ISCs), ISCs are the only dividing cells in the midgut and are responsible for maintaining midgut homeostasis and regeneration, The ISC division gives rise to a renewed stem cell and an enteroblast, which can differentiate into secretory enteroendocrine cells or absorptive enterocytes, Intrinsic factors such as Tuberous Sclerosis Complex and Myc coordinate the growth and division of ISCs, Extrinsic factors such as Epidermal Growth Factor from surrounding cells and the interaction with basement membrane also regulate the rate of ISC division, Insulin secreted from CNS function as a long-range growth factor to control ISC activity and therefore intestinal tissue homeostasis
Reviewed at 2017/09/25